2013
DOI: 10.1158/1055-9965.epi-12-0917-t
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Load in Eyebrow Hair Follicles and Risk of Cutaneous Squamous Cell Carcinoma

Abstract: Background: Beta-human papillomavirus (betaPV) may play a role in the development of cutaneous squamous cell carcinoma (SCC). However betaPV is highly prevalent, and it may only be people with a higher viral load who have increased risk of SCCs. We therefore examined the association between betaPV load and SCCs.Methods: We recruited 448 immunocompetent cases with SCCs and 464 controls from Italy and Australia and 497 immunosuppressed organ transplant recipients (OTR; 179 cases and 318 controls) from Europe. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 27 publications
2
86
0
1
Order By: Relevance
“…Briefly, PM-PCR was performed in a final reaction volume of 50 ml, containing 10 ml of the isolated DNA, 2.5 mM MgCl 2 , 1Â GeneAmp PCR buffer II, 0.2 mM deoxynucleoside triphosphates, 1.5 U Amplitaq Gold DNA polymerase and 10 ml of the PM primer mix. The PCR was performed by a 9-min preheating step at 94 1C, followed by 35 …”
Section: B-hpv Dna Detection and Genotyping With The Pm-pcr Reverse Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, PM-PCR was performed in a final reaction volume of 50 ml, containing 10 ml of the isolated DNA, 2.5 mM MgCl 2 , 1Â GeneAmp PCR buffer II, 0.2 mM deoxynucleoside triphosphates, 1.5 U Amplitaq Gold DNA polymerase and 10 ml of the PM primer mix. The PCR was performed by a 9-min preheating step at 94 1C, followed by 35 …”
Section: B-hpv Dna Detection and Genotyping With The Pm-pcr Reverse Hmentioning
confidence: 99%
“…Seroepidemiological studies have associated skin cancer in organ transplant recipients with the presence of anti-b-HPV antibodies, and PCR-based studies have identified b-HPV DNA in over 80% of skin tumors from these patients. 22,[35][36][37][38][39][40][41][42][43] Despite these findings, a causal role of these viruses has been difficult to verify because of their ubiquitous prevalence in the general population and their absence in some cancers. 25,44 The major weakness of the available studies is that the proposed association is mostly based on the presence of viral DNA in tumor tissues or positive antibody responses.…”
mentioning
confidence: 99%
“…Serum was collected and tested for 16 βPV, 6 γPV, 4 αPV, 2 μPV, and 1 νPV IgG antibodies with a multiplex serology technique based on glutathione s‐transferase capture ELISA in combination with fluorescent bead technology 37, 38. All 3 techniques used have been previously described in more detail 25, 32, 35, 36, 37, 38…”
Section: Methodsmentioning
confidence: 99%
“…A substantial body of epidemiologic data show an association between HPV infection and cSCC,12, 20, 21, 22, 23, 24 in particular, in OTRs 25, 26. In most studies, HPV infection has been determined by detection of serologic responses to a large series of βPV and sometimes γPV types12, 21, 22, 23, 25, 26, 27, 28, 29, 30, 31 and less frequently by detecting genomic DNA from 1 or multiple HPV types in eyebrow hair or skin scrapings 20, 21, 25, 32, 33, 34…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation